ANALISIS SENSITIVITAS BEBERAPA WILAYAH DI PAPUA BARAT TERHADAP FENOMENA ENSO - Aries Astradhani Subgan (Jurnal Natural, 2014)
Inter-annual climate variability (ENSO) become major issues for sciences for nowadays because the effect of globally. The purpose of this research is to know the characteristic of the climate on West Papua Region that can investigate and to know variable of the responds to every area of the ENSO phenomena. This is use for the climate parameter for rainfall and sea surface temperature (SST). Technic analysis begins to see periodicities rainfall using wavelet transformation. Next, analysis percentage of rainfall on the phases of ENSO Cases to see how big the influence of ENSO to the Increasing and Decreasing of rainfall in every region. Next step is to use statistic technical to see the connection between rain drop variable into the Standardized Precipitation Index (SPI) to the ENSO index. The result of wavelet analysis to the rainfall showed the domination of periodicities in one year, this indicated that the research area is effected by monsoon and local factors. The result of rain fall percentage and linier correlation analysis of ENSO index to the SPI in each territorial in general showed the ENSO influence. This can be shown by negative correlation score that means, when there is an EL NINO (La Nina) in Pacific Ocean at the same time there is a decreasing or increasing of rainfall in research territorial. The variation in each location responds showed the ENSO effect doesn’t have to influence directly to the rain fall in the research zone.